Ergebnisse der Albanien-Expedition 1961 des ’Deutschen Entomologischen Institutes’. 85. Beitrag. Coleoptera: Endomychidae. - Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1971)
A survey of the distribution of the Endomychidae of the Balkan peninsula(40 species) is given, and the 8 species known so far from Albania are revised, 5 according to accessible material and 3 according to publications only; Lycoperdina pulvinata Reitter collected by the Albania by Deutsches Entomologisches Institut, was found for the first time in Albania.